Effect of Diabetic Education for the Group Along with Individual Nutrition Counseling on Dietary Intake: Effectiveness of Diabetes Management Education on Dietary Intake and Clinical Profile of Children with Diabetes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study was conducted to determine the dietary intake and clinical profile of children with diabetes and to investigate the effects of diabetes management education interventions on disease management. The total sample consisted of 132 subjects, including 82 subjects from PMBAH and 50 subjects from SH South Riyadh capital. Of the 132 subjects selected for the study, 129 had type 1 diabetes mellitus (T1DM) and 3 had type 2 diabetes mellitus (T2DM). Subjects ranged in age from 1 to 18 years. A pre-interview program was conducted on the subjects to collect necessary information. Subjects mean energy and macronutrient (CHO, protein and fat) consumption was calculated based on the 3-day dietary fortification approach and compared with the RDA. It was found that the CHO intake was significantly increased compared with the RDA. The subjects' diets were also deficient in calories and protein. All subjects (n = 81) over 10 years of the total sample were selected for the diabetes education-based intervention program. After 12 weeks of intervention, 40 subjects continued the program while the rest dropped out. At the end of the intervention period, significant improvements in their food intake, HbA1c levels and quality of life were noted. However, the concept of setting insulin doses based on CHO numbers did not work because subjects were unable to fix their insulin bolus doses based on CHO numbers.